Benthonic Opisthobranch species (Mollusca: Gastropoda) from the Northern Peruvian Coast - Nakamura, Katia (2006)
The benthonic opisthobranch species reported for Northern Perú are presented here. The aim of the study is to show the species diversity of benthic opisthobranchs found in the northern coast, show the importance of their study and. awake the interest on these taxa. This work is based on a literature recompilation from all studies available in the matter showing reported species for the area of interest. Seventeen species previously known for the northern coast, classiﬁed for the Informal Group Opisthobranchia within 6 clades, 12 families and 14 genera are shown. In spite of the high diversity potential that the area of study shows, relatively low numbers of species are found due to the scarce research in the matter.